Factors Associated With Low Birth Weight Among Under‐Five Children in Sub‐Saharan Africa: Evidence From Demographic and Health Surveys of 58,857 Children - Sulaimon T. Adedokun; Sanni Yaya (Health Science Reports)
ABSTRACT Background and Aims Low birth weight has become one of the major health challenges in the world with 19.8 million newborns suffering from it in 2020. Such children stand the risk of dying in their first month of life or are at a high risk of stunted growth, low intelligent quotient and other health challenges as they grow into adulthood. Despite efforts made so far in reducing the proportions of children with low birth weight, the problem persists in sub‐Saharan Africa. This study examined the factors associated with low birth weight among under‐five children in sub‐Saharan Africa. Methods This study used data sets from Demographic and Health Surveys (DHS) of 15 countries in sub‐Saharan Africa. About 58,857 children were involved in the study. Binary logistic regression was used to examine the factors associated with low birth weight at multivariable level. Results Prevalence of low birth weight was 10% in sub‐Saharan Africa with Mauritania (22.9%), Mali (16.5%) and Madagascar (12.2%) having the highest rates. It is most prevalent among children whose mothers have no education (11%), not working (11.5%) and had less than 4 ANC visits (11.4%). The odds of low birth weight increased significantly for children whose mothers belonged to middle and poor households, have no education, were not employed and had less than 4 ANC visits. Female children, children of first order birth and those that belonged to households with unsafe method of stool disposal were more likely to suffer from low birth weight. Conclusion The study has revealed that 1 in every 10 children in sub‐Saharan Africa suffered from low birth weight. There is a need for an urgent intervention that would reduce the proportion of children with low birth weight in the region. Such interventions should incorporate efforts to promote female adult and girl‐child education and individual and household socioeconomic status.